Antimicrobial properties of Ag + loaded zeolite polyester polyurethane and silicone rubber and long-term properties after exposure to in- vitro ageing - Kaali, Peter; Strömberg, Emma; Aune, Ragnhild E.; Czél, György; Momcilovic, Dane; Karlsson, Sigbritt (Polymer degradation and stability, 2010)
In biomedical applications, tubes (e.g. catheters etc.) are commonly produced from polyurethane (PU) and silicone rubber which are known to be biocompatible materials. Several studies have shown that tubes, which are connected to the body (invasive) (especially urinary, tracheotomy and central venous catheters) are associated with infections. The present study reports the development of a new method aiming at obtaining antibacterial properties for PU and silicone rubber by mixing respective material with a natural antibacterial agent (Ag+ loaded zeolite) in different weight fractions. The influence of the zeolite content on the antimicrobial properties were analysed by exposure to bacteria (ISO 22196) and mixtures of fungi (ISO 846). The materials were also subject to artificial body fluids (Artificial Lysosomal Fluid (ALF) and Gamble’s solution) for periods up to three months and the subsequent changes in the chemical properties after in-vitro exposure were determined by Matrix Assisted Laser Deposition/Ionization Time Of Flight Mass Spectrometry (MALDI-TOF MS) and Attenuated Total Reflection Fourier Transform Infra Red spectroscopy (ATR-FTIR). It was established that the antimicrobial effect of the materials increased with the increase of the zeolite content. The wettability of the materials was found to decrease significantly during the in-vitro exposure, but this could not be correlated to the zeolite content. In the PU samples, the formation of free carbonyl and –OH groups was observed, which corresponds to oxidative degradation. In case of the silicone rubber the ratio of cyclic PDMS to linear PDMS (H, CH3 and dimethyl terminated) decreased, which indicates a change in the concentration of the compounds. The formation and increase of the O–H bond during the exposure was also confirmed by the infrared spectra of the material which corresponds to hydrolysis of the silicone rubber.